The Verb *√L(-)Đ 'To Remove' in Early Aramaic Curses and the Evolution of Aramaic Interdental Orthography and Phonology. (17th February 2020) - Richey, Madadh
Abstract: Several verbal morphologies including the core orthography ld are attested in ninth- and eighth-century bce Aramaic texts from Sefire and Tell Fekheriyeh. From their similar contexts, all can be demon-strated to have the semantics 'to remove', but scholars are divided as to the root source and precise phonology of these verbs. The present paper demonstrates that these ld verbs belong to a cognate set descendant from proto-Semitic . The representation of the reflex of the interdental by d is a precocious development only attested broadly in later Aramaic, but its surfacing here can be ration-alized by appeal to diachronic phonology, phonotactics and linguistic typology. The consistent employment of developed orthography for this root is perhaps related to the existence of a broad and consistent early Aramaic curse tradition.